GE_GERICHTE C/15947/2016 vom 15. Februar 2019 - GE Cour de justice (2019)
RÉSILIATION IMMÉDIATE ; VACANCES ; TORT MORAL | CO.337.al1; CO.337.al2; CO.321a.al1; CO.337c.al3; CO.329d.al2; CO.328.al1; CO.49.al1